Knowledge, and practices on sexual and reproductive health among youth trainees attached to youth training centers in Sri Lanka - D. Mataraarachchi; P. V. S. C. Vithana; A. Lokubalasooriya; C. J. Jayasundara; A. S. Suranutha; T. E. A. Pathirana; C. De Silva (Contraception and Reproductive Medicine, 2023)
Abstract Background Sexual and reproductive health is a major concern among adolescents and youth in Sri Lanka. The study was carried out to assess the knowledge, and practices of the youth trainees attached to youth training institutes in Sri Lanka. Methodology A descriptive, cross-sectional study was carried out among randomly selected 425 youth trainees attached to youth training centers in Sri Lanka using a pre-tested self-administered questionnaire. Statistical analysis was conducted using SPSS-21. Categorical variables were presented as numbers and percentages. A comparison of categorical variables was conducted using the Chi-Square test and Fisher’s exact test as applicable. The bivariate logistic regression model was used to determine the independent association of the selected demographic factors with youth trainees’ sexual and reproductive health knowledge. Results Study group consisted of 51.8% (n = 220) males and 48.2% (n = 205) females with a mean age of 18.6 years (SD = 1.8). Youth trainees’ knowledge of the physiology of the reproductive tract was not at a satisfactory level, where Only 49% (n = 211) knew that nocturnal emission is normal in young men. The trainee’s knowledge of contraception was also at a poor level. Only 47.5% (n = 202) had ever heard of condoms, and 13.2% (n = 56) knew about the emergency contraceptive pill. Nearly 8% (n = 33) of the youth had engaged in sexual intercourse at least once in their lifetime. Male gender (AOR = 2.3, p < 0.001), and age above 20 years (AOR = 1.9, P = 0.005) were positively associated with SRH knowledge. Conclusions and recommendations Knowledge and practices on sexual and reproductive health among youth trainees were sub-standard. The study recommends strengthening sexual and reproductive health education at youth training centers.